Catalytic Asymmetric Synthesis of Cyclic Sulfamides from Conjugated Dienes - Cornwall, Richard G; Zhao, Baoguo; Shi, Yian (Organic letters, 2013)
This paper describes the catalytic asymmetric diamination of alkyl dienes using N,N′-di-tert-butylthiadiaziridine 1,1-dioxide in the presence of Pd(0) and a chiral phosphoramidite ligand to give cyclic sulfamides in high yield and high ee. The diamination is also amenable to gram scale.